The Correlation between Happiness Level and The Sustainibility of Urban Kampung in Malang - Ratih Ikawaty; Surjono Surjono (Sekolah Pascasarjana Universitas Brawijaya, 2017)
Indonesian happiness index was released in 2013 being the representation of happiness of the Indonesian population. Indonesia conforms that sustainable development is a future development objective is the goal of future development as the happiness achievement of Indonesian society is supported by several economic, social and environmental indicators which are the main components of the sustainable development concept. Significantly the happiness index has a positive relationship with the sustainability achievement, cities that meet the criteria of sustainable development can provide greater opportunities for the community to achieve happiness. This study evaluated the happiness of the villagers with the happiness index and fuzzy logic approach, then analyzed the relationship between the level of happiness of the villagers using sustainability of the kampung. The result of this study indicates that the level of happiness has a linear relationship with the sustainability, this can be seen from the happiness level of Kampung Sukun at 0.51 (happy) correlates with the sustainability level at 0.68 (medium high sustainability) while for Kampung Kebalen has a happiness level at 0.48 (less than happy) with sustainability level at 0.45 (medium sustainability). These two values indicate the linearity of the relationship between the happiness index and the levels of sustainability of the kampungs.